Fine Tuning of an Oxidative Stress Model with Sodium Iodate Revealed Protective Effect of NF-κB Inhibition and Sex-Specific Difference in Susceptibility of the Retinal Pigment Epithelium - Xue Yang; Usha Rai; Jin-Yong Chung; Noriko Esumi (MDPI AG, 2021)
Oxidative stress of the retinal pigment epithelium (RPE) is a major risk factor for age-related macular degeneration (AMD). As a dry AMD model via oxidative stress, sodium iodate (NaIO3), which is primarily toxic to the RPE, has often been used at a high dose to cause RPE death for studying photoreceptor degeneration. Thus, characterization of RPE damage by a low dose of NaIO3 is still limited. To quantify RPE damage caused by NaIO3 in mice, we recently developed a morphometric method using RPE flat-mounts. Here, we report that NaIO3 has a narrow range of dose-effect correlation at 11-18 mg/kg body weight in male C57BL/6J mice. We evaluated the usefulness of our quantification method in two experimental settings. First, we tested the effect of NF-κB inhibition on NaIO3-induced RPE damage in male C57BL/6J mice. IKKβ inhibitor BAY 651942 suppressed upregulation of NF-κB targets and protected the RPE from oxidative stress. Second, we tested sex-specific differences in NaIO3-induced RPE damage in C57BL/6J mice using a low dose near the threshold. NaIO3 caused more severe RPE damage in female mice than in male mice. These results demonstrate the usefulness of the quantification method and the importance of fine-tuning of the NaIO3 dose. The results also show the therapeutic potential of IKKβ inhibition for oxidative stress-related RPE diseases, and reveal previously-unrecognized sex-specific differences in RPE susceptibility to oxidative stress.